Heart Transplantation in Children With Down Syndrome - Justin Godown; Darlene Fountain; Neha Bansal; Rebecca Ameduri; Susan Anderson; Gary Beasley; Danielle Burstein; Kenneth Knecht; Kimberly Molina; Sherry Pye; Marc Richmond; Joseph A. Spinner; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Children with Down syndrome (DS) have a high risk of cardiac disease that may prompt consideration for heart transplantation (HTx). However, transplantation in patients with DS is rarely reported. This project aimed to collect and describe waitlist and post– HTx outcomes in children with DS. Methods and Results This is a retrospective case series of children with DS listed for HTx. Pediatric HTx centers were identified by their participation in 2 international registries with centers reporting HTx in a patient with DS providing detailed demographic, medical, surgical, and posttransplant outcome data for analysis. A total of 26 patients with DS were listed for HTx from 1992 to 2020 (median age, 8.5 years; 46% male). High‐risk or failed repair of congenital heart disease was the most common indication for transplant (N=18, 69%). A total of 23 (88%) patients survived to transplant. All transplanted patients survived to hospital discharge with a median posttransplant length of stay of 22 days. At a median posttransplant follow‐up of 2.8 years, 20 (87%) patients were alive, 2 (9%) developed posttransplant lymphoproliferative disorder, and 8 (35%) were hospitalized for infection within the first year. Waitlist and posttransplant outcomes were similar in patients with and without DS (P=non‐significant for all). Conclusions Waitlist and post‐HTx outcomes in children with DS selected for transplant listing are comparable to pediatric HTx recipients overall. Given acceptable outcomes, the presence of DS alone should not be considered an absolute contraindication to HTx.